Childhood Asthma and Allergies in Urban, Semiurban, and Rural Residential Sectors in Chile - Kausel, Leonie (Hindawi Publishing Corporation, 2013)
While rural living protects from asthma and allergies in many countries, results are conflicting in Latin America. We studied the prevalence of asthma and asthma symptoms in children from urban, semiurban, and rural sectors in south Chile. A cross-sectional questionnaire study was conducted in semiurban and rural sectors in the province of Valdivia (n = 559) using the ISAAC (International Study of Asthma and Allergies in Childhood) questionnaire. Results were compared to prevalence in urban Valdivia (n = 3105) by using data from ISAAC III study. Odds ratios (+95% confidence intervals) were calculated. No statistical significant differences were found for asthma ever and eczema symptoms stratified by residential sector, but a gradient could be shown for current asthma and rhinoconjunctivitis symptoms with urban living having highest and rural living having lowest prevalence. Rural living was inversely associated in a statistical significant way with current asthma (OR: 0.4; 95% CI: 0.2–0.9) and rhinoconjunctivitis symptoms (OR: 0.3; 95% CI: 0.2–0.7) in logistic regression analyses. Rural living seems to protect from asthma and respiratory allergies also in Chile, a South American country facing epidemiological transition. These data would be improved by clinical studies of allergic symptoms observed in studied sectors.